2015
DOI: 10.1016/j.acra.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Development and Progression of Thoracic Aorta Calcification

Abstract: Background Vascular calcification independently predicts cardiovascular disease (CVD) and computed tomography (CT) is a useful tool to evaluate and quantify not only coronary but also thoracic aortic calcification (TAC). Previous TAC progression reports were limited to dialysis and renal transplant patients. This is the first study to evaluate TAC progression in a large multi-ethnic cohort without clinically evident CVD at entry. Methods Non-contrast enhanced cardiac CT were obtained in 5886 of 6814 MESA par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
2
21
2
Order By: Relevance
“…Taking the strong association of thoracic aortic with coronary calcification into account, the identification of main determinants for TAC incidence and progression may play a pivotal role in cardiovascular prevention. In a multiethnic population‐based cohort, Youssef et al found age, systolic blood pressure, intake of antihypertensive medication, and smoking to be associated with TAC i , thus not discriminating between the ascending and descending thoracic aorta . Accordingly, our results reveal—aside from age and sex—systolic blood pressure and LDL‐C as the main determinants of TAC i , especially in the ascending aorta.…”
Section: Discussioncontrasting
confidence: 68%
“…Taking the strong association of thoracic aortic with coronary calcification into account, the identification of main determinants for TAC incidence and progression may play a pivotal role in cardiovascular prevention. In a multiethnic population‐based cohort, Youssef et al found age, systolic blood pressure, intake of antihypertensive medication, and smoking to be associated with TAC i , thus not discriminating between the ascending and descending thoracic aorta . Accordingly, our results reveal—aside from age and sex—systolic blood pressure and LDL‐C as the main determinants of TAC i , especially in the ascending aorta.…”
Section: Discussioncontrasting
confidence: 68%
“…Results from the Multi-Ethnic Study of Atherosclerosis (MESA) also showed the age, SBP, smoking, LDL, HDL, and creatinine were related to the incident CAC risk [18, 19]. In our study, the SBP in noninitiation group were controlled better than that in initiation group, which reveal the role of blood pressure in initiating the CAC in PD patients.…”
Section: Discussionsupporting
confidence: 59%
“…Calcification within the aorta has been established as a risk factor for cardiovascular morbidity and mortality 11,12 . Also multiple conventional risk factors, including age, blood pressure and smoking, are associated with aortic calcification 13 . We 14 and others 1519 have reported a significant positive association between aortic calcification and arterial stiffness in cross-sectional data of healthy population 14,16,19 , as well as in patients with isolated systolic hypertension 17 , peripheral arterial disease 20 and chronic kidney disease 21 .…”
Section: Introductionmentioning
confidence: 99%